Drug metabolism and pharmacokinetic strategies for oligonucleotide- and mRNA-based drug development. Issue 10 (October 2018) - Andersson, Shalini; Antonsson, Madeleine; Elebring, Marie; Jansson-Löfmark, Rasmus; Weidolf, Lars
Graphical abstract: Highlights: Synthetic development of modified nucleotides improves DMPK and pharmacodynamics. Understanding cellular uptake mechanisms will improve targeted drug delivery. Preclinical animal data scale well to humans, supporting dose-setting in clinical trials. Improved bioanalytical sensitivity is needed to establish long elimination half-lives. Mastering oral delivery will fuel interest from the industry and boost science. Abstract : Oligonucleotide and modified mRNA therapeutics have great potential to treat diseases that are currently challenging to cure and are expanding into global and chronic disease areas such as cancer and various cardiovascular diseases. Advanced drug delivery systems or ligand–drug conjugates are utilized to achieve 'the right dose to the right target' to benefit efficacy and safety in patients. Chemistry and ADME characteristics distinguish these therapeutics from small molecules. Understanding the scalability and translatability between species and compound properties is crucial for robust nonclinical PKPD predictions to support clinical study design. Although the field has been developing for three decades, there is still room for innovation but also a need for nonclinical regulatory guidance to address these new modalities. Teaser: Oligonucleotide-based therapeutics show great clinical promise and drug metabolism and pharmacokinetic understanding will be key to expand into broader patient populations.